Design and creation of a web-based extracurricular information system using the laravel framework at ksatrya High school - Agustina, Salma Rizka Agustina; Ulan Bani, Alexius; Galih W, Raditya (Yayasan Bina Internusa Mabarindo, 2024)
Extracurricular activities are activities that are held outside of class hours listed in the composition of the student activity program. Ksatrya High School is an educational institution under the care of the Perguruan Ksatrya Foundation. currently, the management of extracurricular data and registration of students who take part in extracurricular activities is still carried out manually, namely recording and registration which still uses forms in the form of google forms so that there is no complete information about extracurricular activities. There are no facilities available in managing extracurricular activities at school due to lack of utilization of information technology. Therefore, to handle these problems, a web-based extracurricular information system was created with system modeling using the Unified Modeling Language (UML), the Laravel framework as a programming language and MySQL as a database, so as to help and facilitate the management of extracurricular activities at Ksatrya High School.